Flow-Excited Turbine Rotor Instability - Andrew D. Dimarogonas; Julio C. Gomez-Mancilla (International Journal of Rotating Machinery)
The problem of steam whirl is one of the technological limits that now prohibit the development of power-generating turbomachinery substantially above GW. Due to steam flow, self-excited vibrations develop at high loads in the form of stable limit cycles that, at even higher loads, deteriorate to chaotic vibration of high amplitude.